2006
DOI: 10.1080/13697130600997775
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different preparations of hormone therapy on sexual dysfunction in naturally postmenopausal women

Abstract: Tibolone has more positive effects on the sexual dysfunction of postmenopausal women and may be an alternative to the E2/dienogest preparation in postmenopausal women with sexual dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…We did not measure physiological parameters directly but instead asked questions relating to menopause, hormone therapy, contraceptives, age, and health. There may be differences in the ways in which certain hormones (and combinations of hormones) [26,27] and particular classes of antidepressants may affect a woman's sexual response [28]. We did not differentiate between these drug classes because we did not have the statistical power for such a fine‐grained analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure physiological parameters directly but instead asked questions relating to menopause, hormone therapy, contraceptives, age, and health. There may be differences in the ways in which certain hormones (and combinations of hormones) [26,27] and particular classes of antidepressants may affect a woman's sexual response [28]. We did not differentiate between these drug classes because we did not have the statistical power for such a fine‐grained analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Women with urogenital discomfort are usually reluctant to be involved in sex. On the other hand HT is an effective option to improve vaginal lubrication and mood, and hence reduce painful intercourse [25,26]. Female education predicts a positive attitude toward sex and HT use [22,27].…”
Section: Discussionmentioning
confidence: 99%
“…Tibolone is a synthetic steroid with estrogenic, progestagenic, and androgenic properties. Studies have suggested a positive effect on sexual function with use [145,146].…”
Section: Medical Treatment Of Fsdmentioning
confidence: 99%